The study of thermal field of an object represented in the basis of green functions - Kulinchenko, Georgіy; Mozok, Evgen (Eastern-European Journal of Enterprise Technologies, 2016)
Existing means of thermal field modeling for the construction of the real time spatial distribution of the field were analyzed. The expediency of using the method of integral transformations for solving heat conduction problems was shown. Based on the comparison of methods of thermal fields construction method of integral transformations in the basis of the Green's functions was chosen. Construction of Green's functions for the use in the experimental facility is performed by the method of Laplace integral transforms. Software, generated based on the use of Matlab environment, allows to adjust the visualized field pattern by actual measured temperature values. Temperature point values of the experimental facility field were measured by NAT thermocouples, that are connected to a PC through OWEN 150UM controller interface, which makes it possible not only to form an array of measured values of the temperature, but also to adjust the time-varying boundary conditions of the calculated heat equation. The main purpose of the research is to assess the performance of the developed algorithms to reduce the field frame modeling time, which would allow to use the resulting pattern of the thermal field distribution in the industrial thermal facilities control process. The advantage of the thermal field constructing algorithm in the basis of the Green's function is the ability of the independent calculation of all points of the investigated area, allowing in the future to speed up the computation by applying high-performance computing.